Release of Liposomal Contents by Cell-Secreted Matrix Metalloproteinase-9 - Banerjee, Jayati (2009)
Liposomes have been widely used as a drug delivery vehicle and currently, more than 10 liposomal formulations are approved by the Food and Drug Administration for clinical use. However, upon targeting, the release of the liposome-encapsulated contents is usually slow. We have recently demonstrated that contents from appropriately-formulated liposomes can be rapidly released by the cancer-associated enzyme matrix metalloproteinase-9 (MMP-9). Herein, we report our detailed studies to optimize the liposomal formulations. By properly selecting the lipopeptide, the major lipid component and their relative amounts, we demonstrate that the contents are rapidly released in the presence of cancer-associated levels of recombinant human MMP-9. We observed that the degree of lipid mismatch between the lipopepides and the major lipid component profoundly affects the release profiles from the liposomes. By utilizing the optimized liposomal formulations, we also demonstrate that cancer cells (HT-29) which secrete low levels of MMP-9 failed to release significant amount of the liposomal contents. Metastatic cancer cells (MCF7) secreting high levels of the enzyme rapidly release the encapsulated contents from the liposomes.